Synthesis and biological evaluation of chalcones and derivatives in vitro against AGP01 cell (Research, Society and Development, 2021)
The interest in obtaining chalcones is due to the numerous pharmacological activities described in the literature for these compounds that are intermediates in the biosynthesis of flavonoids. Thus, the synthesis and characterization of several chalcones and derivatives become important for the development of compounds with antiproliferative activity. In this work, ten substances were synthesized, seven chalcones and three naphthoflavanones, obtained by the Claisen Schmidt aldol condensation reaction between acetophenones and aldehydes, at room temperature conditions in a basic medium. Yields ranged between 65.35% and 97.45%. Being characterized and confirmed through ¹H and ¹³C NMR spectroscopic techniques in comparison with literature data. All synthesized products were submitted to the cytotoxicity assay of 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium (MTT) bromide, to evaluate the antiproliferative activity in vitro, in gastric tumor lineage (AGP01), compared to the normal lung cell line (MRC-5). The most active substances were chalcones 2, 6, 3, 4 and 1, which showed the greatest reduction in cell viability of AGP01, being greater than 90%.